2015
DOI: 10.1002/cctc.201500517
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Magnetically Recyclable Molybdenum Disulfide Catalyst for Direct Hydrodesulfurization

Abstract: Superparamagnetic MoS2/SiO2/Fe3O4 catalysts that consist of magnetite as the core, silica as the covering layer, and molybdenum sulfide as the top layer were prepared in easy steps. Two different surfactants (anionic and cationic) were used to assist with the synthesis of two of the samples, and one sample was prepared without surfactant. The surfactant was found to have a significant effect on the properties and activity of the final catalysts. Hydrodesulfurization (HDS) tests of the catalysts show higher act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…21,34,48 4,6-DMDBT was also employed to further evaluate the adsorption performance of the obtained BN mesoporous nanowires at 298 K. As is well-known, owing to its aromaticity and steric hindrance of the two methyl, 4,6-DMDBT was difficult to removed through hydrodesulfurization, oxidative desulfurization, or extractive desulfurization. 49,50 Hence, it is greatly important to remove 4,6-DMDBT. As shown in Figure 10, the BN mesoporous nanowires could also display excellent adsorption performance for 4,6-DMDBT (400 ppm initial sulfur concentration), and the adsorption capacity could reach 33.2 mg S g −1 adsorbent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21,34,48 4,6-DMDBT was also employed to further evaluate the adsorption performance of the obtained BN mesoporous nanowires at 298 K. As is well-known, owing to its aromaticity and steric hindrance of the two methyl, 4,6-DMDBT was difficult to removed through hydrodesulfurization, oxidative desulfurization, or extractive desulfurization. 49,50 Hence, it is greatly important to remove 4,6-DMDBT. As shown in Figure 10, the BN mesoporous nanowires could also display excellent adsorption performance for 4,6-DMDBT (400 ppm initial sulfur concentration), and the adsorption capacity could reach 33.2 mg S g −1 adsorbent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The carbon contents in the samples was due to the presence of surfactant in the catalyst structure. As shown in our previous work, the surfactant CTAC plays two important roles. First, it assists with anchoring MoS 2 on the surface of the greigite core and second, it functions as a scaffold platform to support the MoS 2 crystalline in the synthesis to form a core‐shell structure.…”
Section: Resultsmentioning
confidence: 71%
“…Recently, we showed a novel way to incorporate Fe 3 O 4 particles as magnetic carriers to synthesize a MoS 2 composite with magnetic properties . The composite showed an excellent ability in removing sulfur mainly through the direct desulfurization pathway (DDS).…”
Section: Introductionmentioning
confidence: 99%
“…CTAC also has a scaffold effect during the formation of MoS 2 crystals. A hydrothermal method was applied for the synthesis of (Co or Ni)MoS 2 in this study, details of which can be found elsewhere . Briefly, sodium sulphide (0.21 g of nonahydrate crystals) was dissolved in DIW (5 mL).…”
Section: Methodsmentioning
confidence: 99%